2021
DOI: 10.1371/journal.pone.0260187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SARS-CoV-2 in semen, seminal plasma, and spermatozoa pellet of COVID-19 patients in the acute stage of infection

Abstract: To date, there is limited information about the presence of SARS-CoV-2 in semen especially in the acute phase of the infection. While available data from cohort studies including a total of 342 patients in the acute or recovery phase of the infection are reassuring, one study mentioned detecting virus in the semen of 6/38 COVID-19 patients. Here we assessed SARS-CoV-2 presence in the semen of COVID-19 positive patients in the acute stage of infection, within 24 hours of the positive nasopharyngeal swabs. Semen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…To date, there are only two studies that found SARS‐CoV‐2 in semen specimens. These patients were in acute stage of infection or recovering from severe disease [21, 22]. However, another study analyzing semen samples obtained in acute stage of the infection did not detect SARS‐CoV‐2 in semen [23].…”
Section: Sars‐cov‐2 In Semen Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are only two studies that found SARS‐CoV‐2 in semen specimens. These patients were in acute stage of infection or recovering from severe disease [21, 22]. However, another study analyzing semen samples obtained in acute stage of the infection did not detect SARS‐CoV‐2 in semen [23].…”
Section: Sars‐cov‐2 In Semen Specimensmentioning
confidence: 99%
“…Hormonal levels restored after treatment [33] Semen of COVID-19 patients No detection of SARS-CoV-2 RNA in the semen of COVID-19 patients, including semen samples from two patients with an acute COVID-19 infection. Subjects with a moderate infection showed an impairment of sperm quality [24] Semen of COVID-19 patients SARS-CoV-2 was not detected in semen sample of patients in the acute phase of the infection [23] Semen of COVID-19 patients SARS-CoV-2 was detected in semen sample of patients in the acute phase of the infection or recovering from severe disease [21] Semen of patients recovering from COVID-19 SARS-CoV-2 was detected in semen sample of just 1 out of 32 patients [22] Blood from COVID-19 patients Lower total testosterone (TT), calculated free T (cFT), were found in the transferred to intensive care unit (ICU)/deceased patients [18] Semen of patients affected by COVID-19…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Numerous studies have failed to identify virus in male and female reproductive organs of infected patients [45][46][47]. However, a more recent study detected the virus in vaginal swabs of two out of 35 women with COVID-19 [21], and two groups have reported virus in semen of infected men [19,20]. For example, a study by Li and colleagues found that six of 38 male COVID-19 patients had detectable levels of SARS-CoV-2 in their semen [19].…”
Section: Discussionmentioning
confidence: 99%
“…Within the female and male reproductive systems, expression of SARS-CoV-2 entry factors is present in cells of the ovaries, uterus, vagina, testis, and prostate [7,[15][16][17][18]. Some studies showed detectable virus in the semen of infected males [19,20] and vaginal secretions of infected females [21].…”
Section: Introductionmentioning
confidence: 99%
“…Within the female and male reproductive systems, expression of SARS-CoV-2 entry factors is present in cells of the ovaries, uterus, vagina, testis, and prostate 7 , 15 18 . Some studies showed detectable virus in the semen of infected males 19 , 20 and vaginal secretions of infected females 21 .…”
Section: Introductionmentioning
confidence: 99%